2017
DOI: 10.1103/physrevd.95.074507
|View full text |Cite
|
Sign up to set email alerts
|

Search for low-lying lattice QCD eigenstates in the Roper regime

Abstract: The positive-parity nucleon spectrum is explored in $2 + 1$-flavour lattice QCD in a search for new low-lying energy eigenstates near the energy regime of the Roper resonance. In addition to conventional three-quark operators, we consider novel, local five-quark meson-baryon type interpolating fields that hold the promise to reveal new eigenstates that may have been missed in previous analyses. Drawing on phenomenological insight, five-quark operators based on $\sigma{N}$, $\pi{N}$ and $a_0{N}$ channels are co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…It is concluded that the Roper does not come down from the value calculated with the 3-quark interpolation field alone in this πN scattering calculation. A similar conclusion is reached with mixed 3-quark and 5-quark interpolation fields for the clover fermion at m π = 411 MeV [64]. To understand the results of these πN scattering calculations, we point out that there are other classes of diagrams that will lead to higher Fock space components.…”
Section: Multi-hadron State From Single-hadron Interpolation Fieldsupporting
confidence: 67%
“…It is concluded that the Roper does not come down from the value calculated with the 3-quark interpolation field alone in this πN scattering calculation. A similar conclusion is reached with mixed 3-quark and 5-quark interpolation fields for the clover fermion at m π = 411 MeV [64]. To understand the results of these πN scattering calculations, we point out that there are other classes of diagrams that will lead to higher Fock space components.…”
Section: Multi-hadron State From Single-hadron Interpolation Fieldsupporting
confidence: 67%
“…This evolution is rather insensitive to the mass of the three-quark state which may be as large as 2000 MeV. In view of the difficulties in the quark model to explain the ordering of single-particle states in which the 2s state would lie lower than the 1p state, as well as the recent results of the lattice calculations [28,29] which have not found a sizable three-quark component below 1.65 and 2.0 GeV, respectively, the presented model appears to rule out the existence of a three-quark resonant state around or below 1500 MeV. It favors the picture in which the mass of the S-matrix pole is determined by the energy of the dynamically generated state while its width and modulus are strongly influenced by the three-quark resonant state.…”
Section: Discussionmentioning
confidence: 99%
“…The hunt for the Roper is also a perpetual challenge to lattice QCD which may ultimately resolve the dilemma about the origin of the resonance. Although the picture seems to be clearing slowly [27], the recent calculations of the GrazLjubljana group [28] including besides 3q interpolating fields also operators for πN in relative p wave and σ N in s wave, and a similar calculation by the Adelaide group [29] show, however, no evidence for a dominant 3q configuration below 1.65 and 2.0 GeV, respectively, that could be interpreted as a Roper state. The Graz-Ljubljana group has concluded that πN channel alone does not render a low-lying resonance and that coupling with ππN channels seems to be important, which supports the dynamical origin of the Roper.…”
Section: Introductionmentioning
confidence: 99%
“…[60]. Indeed, meson-baryon operators are often included in the operator basis [60][61][62][63]. Also, results on the Roper reso-nance at almost physical masses [60] suggest the need to map out finite-volume effects in two and three-body coupled channels, namely the πN, f 0 (500)N, π∆, ρN, .…”
Section: Introductionmentioning
confidence: 99%